2016
DOI: 10.1002/pc.24216
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the localization behavior of MWCNTs in binary polymer blends using thermodynamics and viscoelastic approaches

Abstract: Using thermodynamics and viscoelastic approaches, the present work evaluated the localization of multiwalled carbon nanotubes (MWCNTs) in binary polymer blends with matrix/dispersed morphologies from pairs of poly(methyl methacrylate) (PMMA), polystyrene (PS), and polypropylene (PP). Thermodynamic predictions suggested that the MWCNTs should preferentially localize at the blend interface for all the nanocomposite samples. However, viscoelastic measurements showed that the MWCNTs localize elsewhere in the binar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…The carbon nanotubes (CNT) as ideal nanoparticles can add high stiffness and good electrical conductivity to polymer matrices. Additionally, the nanoscale diameter and large aspect ratio of CNT significantly improve the general properties of polymer CNT nanocomposites (PCNT) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The van der Waals attraction between nanotubes leads the aggregation/agglomeration in the nanocomposites, which reduces the filler surface expanse and interrupts the networking level [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The carbon nanotubes (CNT) as ideal nanoparticles can add high stiffness and good electrical conductivity to polymer matrices. Additionally, the nanoscale diameter and large aspect ratio of CNT significantly improve the general properties of polymer CNT nanocomposites (PCNT) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The van der Waals attraction between nanotubes leads the aggregation/agglomeration in the nanocomposites, which reduces the filler surface expanse and interrupts the networking level [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotubes (CNT) have involved significant interest in nanocomposites due to amazing mechanical behavior and good electrical conductivity, as well as nanometer size and high aspect ratio [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. It was reported that only a low content of CNT is enough to prepare a nanocomposite with significant mechanical and conductivity properties.…”
Section: Introductionmentioning
confidence: 99%
“…The wonderful levels of mechanical, electrical, thermal, and physical properties of carbon nanotubes (CNT) have motivated the increasing interests for the investigation of composites containing CNT as polymer/CNT nanocomposites (PCNT) . The electrical conductivity of CNT reaches to 10 6 S/m, but the polymer matrices usually show the conductivity of 10 −16 to 10 −12 S/m .…”
Section: Introductionmentioning
confidence: 99%